2022
DOI: 10.1186/s13223-022-00708-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between constipation and the development of asthma: a meta-analysis

Abstract: Background Constipation has been hypothesized to be associated with the increased risk of wheezing or asthma. However, the relation remains a subject of debate. We conducted this meta-analysis to assess whether constipation influences the risk of wheezing/asthma. Methods PubMed, Embase, and Web of Science were systematically searched for studies published between 1955 and January 2022. Two reviewers independently extracted data and assessed the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, the pathogen dynamics with the microbiota of the gastrointestinal tract is highly complex, and eradication not only affects the gastrointestinal tract itself, but also its absence has been associated with dysbiosis and the emergence of a variety of systemic disorders, weight gain or loss, and susceptibility to allergic diseases such as asthma [43,[74][75][76][77][78][79]. In contrast, research over the years has demonstrated that eradicating H. pylori prior to the onset of precancerous histological changes can prevent the development of gastric cancer and dysbiosis can be managed with the integration to the antibiotic treatment of probiotics and other alternatives for microbiota modulation [80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pathogen dynamics with the microbiota of the gastrointestinal tract is highly complex, and eradication not only affects the gastrointestinal tract itself, but also its absence has been associated with dysbiosis and the emergence of a variety of systemic disorders, weight gain or loss, and susceptibility to allergic diseases such as asthma [43,[74][75][76][77][78][79]. In contrast, research over the years has demonstrated that eradicating H. pylori prior to the onset of precancerous histological changes can prevent the development of gastric cancer and dysbiosis can be managed with the integration to the antibiotic treatment of probiotics and other alternatives for microbiota modulation [80][81][82].…”
Section: Introductionmentioning
confidence: 99%